KLK3 gene rs266882 polymorphism in prostatic tissue. (29th March 2019) - Franco, Joana; Afonso, Fernando; Bernardes, Catarina; Clara Ribeiro, Ana; Maia e Silva, Alexandra
Abstract : Introduction: Prostate cancer is one of most frequent neoplasia in males, affecting the majority of men in the eighth decade of life. It is not yet known what specifically causes prostate cancer, but there are several risk factors for the disease, including age or diet, and it is known that different populations have different risk of developing this cancer. For instance, men in developed countries have higher risk to get this neoplasia and mortality rate is higher in black men, according International Agency for Research on Cancer 2012 data. Prostate cancer can often be detected before symptoms start by testing the amount of prostate-specific antigen (PSA) and is variant forms in a man's blood. However, high levels of this protein do not mean malignancy. So, new biomarkers of this cancer are need. In order to learn more about prostate cancer, we aim to analyze the frequency of ARE-I polymorphism at -158 position of the KLK3 gene in prostatic tissue and the results were compared with other populations frequencies it was done the analysis of the ARE-I polymorphism at -158 position of the KLK3 gene in prostatic tissue and the results were compared with other populations frequencies [1 ]. Materials and methods: In this study it was analysed the rs266882 polymorphism at - 158 position of the KLK3 gene in prostatic tissue from 96 Portuguese individuals diagnosed with prostate cancer and individuals with benign prostatic hyperplasia, from Anatomy Pathology Department of CHBM.The study protocol was previously approved by the hospital ethics committee. PCR-RFLP analysis was performed in DNA extracted from paraffin embedded tissue sections. The allelic and genotype frequencies were analysed and calculated by Hardy-Weinberg R package based on χ 2 –test, with a 95% CI and the results were compared with other ethnic populations from Ensembl Project using a χ 2 test. Results: Samples from the same individual showed the same genotype in cancer and normal tissue, and the genotype found were 48 cases of AA (50%), 35 of AG (36.5%) and 13 GG (13.5%). All frequencies were in Hardy-Weinberg equilibrium (p = 0.119), with allelic frequency of 68, 2% for A and 31.8% for G, being significantly different from African (p < 0.016), European (p < 0.0003), American, South and East Asian (p < 0.0001) population. Obtained genotype frequencies were more comparable to African population (p < 0.0004) than the others ethnic groups. No statistically significant association was showed between genotype and diagnosis. As reported previously [2 ], the result of the association between genotype and the T of tumour stage was nearly statistically significant (p-value = 0.08), and the presence of the A allele showed a statistically significant association with T (p-value = 0.046) but not the G allele. Discussion and conclusions: The allelic and genotype frequencies are closer to the African than European or Asian population, but it wasńt confirm by statistical tests. The African population does not present significant differences from our population to the level of 0.01 for the allelic frequency. The presence of the A allele showed a statistically significant association with T of stage tumor. PSA levels were associated with the tumor volume.